The content of vocational guidance of students in teaching biology - Shaymatov Sayfulla Raxmatullayevich; Pardaboyev Soxib (Genius Journals, 2022)
Vocational guidance work in general secondary schools in our republic is part of the educational and educational process, and the leading role in it falls on the shoulders of the teacher of science. The teacher connects the promotion of the profession with the structure of educational science on an integral and planned basis, while facilitating the student's awareness of various aspects of the world of modern professions.
Keywords: subject; biology; education; schools